PEMANFAATAN LAHAN PEDESAAN UNTUK MEMBUAT SPOT FOTO DI DESA SIGAPITON KECAMATAN AJIBATA - Saloom H. Siahaan; Ayub Januari Sidauruk (Abdi Jurnal Publikasi, 2024)
Sigapiton is one of the villages in Ajibata District, has an area of 72.80 km² (BPS, 2018). Sigapiton Village consists of Hamlet I (Lumban Butar-Butar 1 and Lumban Butar-Butar 2), Hamlet II (Lumban Sirait, Lumban Pea, Lumban Manurung), Hamlet III (Sosor Dolok, Sosor Baringin, Lumban Nauli, Lumban Hasatan). Sigapiton Village has a total of 175 family heads with the assumption that each family has 4-7 people. This is an agricultural sector area such as rice, shallots, corn and the tourism sector. So the author used the land at the location where the service took place, to be used as a photo object or photo spot. The location of this service was carried out in Sigapiton Village, Ajibata District. The reason for choosing this location was the Community Service Lecture (KPPM) program from the MECHANICAL ENGINEERING Study Program.